One Year Pandemic: Community Knowledge and Self-Efficacy in Prevention Behavior of Covid-19 Based on The Health Promotion Model by Nola J. Pender - Hera Hastuti; Kartini Kartini; Annisaa F. Umara; Shieva Nur Azizah; Eriyono Budi Wijoyo; Rizkiyani Istifada (Universitas Aisyah Pringsewu, 2021)
The community has a new adaptation after one year of the COVID-19 pandemic. The concept of Nola J. Pender describes that the behaviour is in line with the knowledge and self-efficacy that an individual possesses. This study aims to analyze the relationship between knowledge, self-efficacy, and behaviour of the community about preventive of COVID-19 after one year of the pandemic. This research is a quantitative study with a cross-sectional method design. Respondents consist of 246 people. Data analysis used chi-square and spearmen tests which were adjusted to the type of variables being analyzed. The results showed that there was good knowledge, positive self-efficacy, and good behaviour in the community in preventing COVID-19 after one year of the pandemic. There is a relationship between self-efficacy and community behaviour in preventing COVID-19, but there is no relationship between knowledge and community behaviour. Other factors also influence the growth of positive community behaviour. Collaboration and commitment from the community and stakeholders are the main factors in harmonizing knowledge and behaviour in preventing COVID-19. Masyarakat memiliki adaptasi baru setelah satu tahun pandemi COVID-19. Model Nola J. Pender mendeskripsikan bahwa perubahan perilaku terjadi seiring dengan adanya pengetahuan dan efikasi diri yang dimiliki individu. Penelitian ini bertujuan untuk menganalisis hubungan pengetahuan, efikasi diri, dan perilaku masyarakat dalam pencegahan COVID-19 setelah satu tahun pandemi. Penelitian ini merupakan studi kuantitatif dengan rancangan metode cross-sectional. Responden yang terlibat dalam penelitian berjumlah 246 orang. Analisis data menggunakan uji chi-square dan spearmen yangdisesuaikan dengan jenis variabel yang dianalisis. Hasil penelitian menunjukkan sebagian besar responden memiliki pengetahuan tinggi, efikasi diri positif, dan perilaku baik masyarakat dalam pencegahan COVID-19 setelah satu tahun pandemi. Ada hubungan antara efikasi diri dengan perilaku masyarakat dalam pencegahan COVID-19, namun tidak ada hubungan antara pengetahuan dengan perilaku masyarakat. Adanya faktor lain yang juga mempengaruhi tumbuhnya perilaku positif masyarakat. Kerja sama dan komitmen masyarakat, serta pemegang kebijakan menjadi faktor utama untuk menselaraskan pengetahuan dan perilaku dalam pencegahan COVID-19.